Colloidal and rheological characterization of SWCNT in biological media. Issue 4 (2nd October 2019) - Cerpa, Arisbel; Lado, Isabel; Quiroga, Oriella; Moreno, Rodrigo; García, Rosario; Cerdán, Sebastián; Abu-Lail, Nehal I.
ABSTRACT: We report on the colloidal and rheological characterization of suspensions of commercial single-walled carbon nanotubes (SWCNT) and oxidized single walled carbon nanotubes (SWCNT-oxi24h), in water and fetal bovine serum (FBS). The effects of two surfactants, dodecyl-benzene sodium sulfonate (SBDS) and sodium dodecyl sulfate (SDS) at different concentrations (0.5–2.0%) on the zeta potential and the rheology of the suspensions is also investigated. SWCNT suspensions were characterized by Transmission Electron Microscopy (TEM) and Atomic Force Microscopy (AFM). The colloidal stability was determined by measurements of zeta potential in the physiological pH range 6.0 < pH <8.0. Rheological measurements were implemented at concentrations of 1 and 1.5 mg/ml, and temperatures of 25°C, 30°C, and 37°C. The results obtained show that SWCNT suspensions in FBS, with and without addition of surfactants, depict a high tendency to aggregate with the bovine serum albumin (BSA), a process we could further characterize using Molecular Dynamics (MD) simulation. SWCNT suspensions in aqueous media show a negative zeta potential between −60 and −80 mV, whereas in FBS the stability is lower, with values of-20 mV. We observed no significant changes in the zeta potential with the different surfactants. The viscosity values obtained are smaller in water than in FBS, demonstrating the higher stability in water. Graphical Abstract: